Analisis Potensi Sektor Ekonomi dan Sektor Basis di Bakorwil Madiun di Empat Kabupaten / Kota - Firda Rahmania; Niniek Imaningsih; Riko Setya Wijaya (OECONOMICUS Journal of Economics, 2022)
The objectives of this study, among others: to determine the economic driving sectors, sectors with higher growth than the same sector, sectors experiencing higher growth from different sectors and basic sectors, in Madiun Regency, Magetan Regency, Ponorogo Regency, and the City of Madiun. The results showed that the sectors that drive in four districts/cities are the information & communication sector, financial services & insurance, education services, health services & social activities. The sector that has shifted a lot in the four regencies/cities in the financial services & insurance sector.